1987
DOI: 10.1016/0077-7579(87)90016-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, biomass, recruitment and productivity of Anadara senilis (L.) (Mollusca: Bivalvia) on the banc d'Arguin, Mauritania

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reasons the number of authors shown on this cover page is limited to 10 maximum. (Haematopus ostralegus), the gastropod Cymbium cymbium and unknown fish species were responsible for a large share of this. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 5 publications
3
28
1
Order By: Relevance
“…We arrive at 8 .1 g AFDW M -2 for Anadara and 8 .9 g for all other species in February-April 1986 . As already explained by Wolff et al (1987) our Anadara value of 8 .1 g pertains only to the area of flats we sampled ; when recalculated for the entire area of tidal flats of the Banc d'Arguin its biomass will be about 5 .5 g AFDW m -2 , which is close to the value by Piersma (1982) . For all other species taken together Piersma (1982 : Table 4 .6) presents biomass values per habitat type similar to ours (Table 6) except for the habitat type of `muddy Zostera' .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We arrive at 8 .1 g AFDW M -2 for Anadara and 8 .9 g for all other species in February-April 1986 . As already explained by Wolff et al (1987) our Anadara value of 8 .1 g pertains only to the area of flats we sampled ; when recalculated for the entire area of tidal flats of the Banc d'Arguin its biomass will be about 5 .5 g AFDW m -2 , which is close to the value by Piersma (1982) . For all other species taken together Piersma (1982 : Table 4 .6) presents biomass values per habitat type similar to ours (Table 6) except for the habitat type of `muddy Zostera' .…”
Section: Discussionsupporting
confidence: 85%
“…Wolff et al (1987) arrived at a value of 0.02 y -' for the large bivalve Anadara senilis at the Banc d'Arguin, but they also concluded that this is an aberrant species . The other fauna largely consists of small species with probably short lifecycles as well as small individuals of large species (see also Piersma, 1982) and hence probably has fairly high P/B ratios (Robertson, 1979 ;Banse & Mosher, 1980) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Now that the phytopigment profiles of sediment samples indicate that on the Banc d'Arguin phytobenthos stocks are possibly not that different from that in nutrient-rich temperate waters, we may have to reconsider the above earlier conclusions. The increase in densities and biomass of A. senilis warrant explanations in terms of reproduction, the recent series of wet years may have triggered successful recruitment (Wolff et al, 1987) and growth. If so, which primary products supported the growing stocks?…”
Section: Molluscan Assemblages and The Benthic Food Chainmentioning
confidence: 98%